Nutritional contribution and sensory profile of panettone enriched with almonds, raisins and dehydrated blueberries - Chiroque Velásquez, Grisel Violeta (Agronomía Mesoamericana, 2023)
Introduction. In Peru, panettone, a brioche-type bread with raisins and candied fruit, is a product of high consumption throughout the year. Its preparation requires a large amount of flour, fat, and sugar, so its excessive consumption contributes to obesity problems and cardiovascular and metabolic diseases. Objective. To determine the nutritional contribution and evaluate the level of acceptance of panettone enriched with almonds, raisins, and dehydrated blueberries, as a healthy alternative, without modifying the characteristic organoleptic attributes recognized by its consumers. Materials and methods. In the physicochemical laboratory of the Universidad de Barranca (Lima, Peru), in December 2019, three types of panettone were formulated replacing the traditional filling with almonds, blond raisins, and dehydrated blueberries for a final composition of 40, 45, and 50 % w/w. They were subjected to sensory evaluation by ranking preference tests to qualify the attributes (color, smell, taste, and texture) and acceptance test with hedonic scale, to qualify the acceptance of the final product. The most acceptable product underwent physicochemical analysis to determine the nutritional contribution of the proposal. Results. The formulation with the highest acceptance was 45 % filler, even though the differences between treatments were not significant (p>0.05) The macronutrient content was similar to what is offered in the market (p>0.05). In relation to micronutrients, a contribution of 8 g of unsaturated fatty acids, 0.36, 5.8, 4.9, 33.3, 9.3, and 109 mg of vitamins B2, B3, E, iron, zinc, and calcium respectively, was observed per 100g g portion. Conclusion. Almonds, blond raisins, and dried cranberries improved the nutritional density of panettone, without significantly affecting the organoleptic characteristics of the product.